Understanding Gold Purchase Decisions: The Role of Customer Satisfaction and Brand Image in Retail Gold Markets - Dewantara, Ibnu Hajar; Mardani, Ronny Malavia; Bastomi, Mohamad (Journal of Regional Economics Indonesia, 2026)
Gold is widely regarded as a stable investment asset, leading to increasing competition among retail gold businesses in attracting consumers. This study aims to examine how brand image and customer satisfaction influence consumers’ gold purchase decisions in a local retail context. A qualitative case study approach was employed to obtain an in-depth understanding of consumer perceptions and experiences. The research was conducted at Toko Emas Sahabat Kraksaan Probolinggo, with informants selected through purposive sampling among consumers who had previously purchased gold. Data were collected through semi-structured interviews, non-participant observation, and documentation, and analyzed using thematic analysis. The findings reveal that brand image plays a crucial role in reducing perceived risk and building consumer trust, while customer satisfaction is primarily shaped by service quality, transparency of information, and product authenticity. Both factors jointly influence consumers’ confidence in making purchase decisions. This study contributes to the consumer behavior literature by highlighting the importance of trust, reputation, and service experience in shaping purchase decisions within the retail gold market.